The relationship between posttraumatic growth and psychological resilience in the covid-19 pandemic: The mediating role of cognitive flexibility and positive schemas - ERDEN ÇINAR, SEVAL (My University, 2022)
The aim of this study was to examine the serial multiple mediator roles of cognitive flexibility and positive schemas in the relationship between posttraumatic growth and psychological resilience of adult individuals in the Covid 19 pandemic. Correlational survey model was used in this study. The sample of the research consists of 329 adult individuals, 233 women (70,8%) and 96 men (29,2%). Personal Information Form, Posttraumatic Growth Inventory, Positive Schema Scale, Cognitive Flexibility Inventory, and The Brief Resilience Scale were used as data collection tools. The research data were analyzed by using SPSS Statistics 21.0 and SPSS Process Macro. In this study, The PROCESS Macro proposed by Hayes was used to conduct serial multiple mediation analysis. According to the findings of the study, the mediator role of cognitive flexibility and positive schemas in the relationship between posttraumatic growth and psychological resilience was found to be statistically significant.

raştırmanın amacı Covid-19 pandemisinde travma sonrası büyüme ile psikolojik sağlamlık arasındaki ilişkide bilişsel esneklik ve pozitif şemaların sıralı çoklu aracı rolünün incelenmesidir. Araştırmada tarama türünde ilişkisel model kullanılmıştır. Araştırmanın örneklemini 233’ü kadın (%70,8), 96’sı erkek (%29,2) toplamda 329 yetişkin birey oluşturmaktadır. Araştırmada veri toplama aracı olarak Kişisel Bilgi Formu, Travma Sonrası Büyüme Envanteri, Pozitif Şema Ölçeği, Bilişsel Esneklik Envanteri ve Kısa Psikolojik Sağlamlık Ölçeği kullanılmıştır. Veriler SPSS Statistics 21.0 ve SPSS PROCESS Makro kullanılarak analiz edilmiştir. Bu çalışmada, sıralı çoklu aracılık analizini yapmak için Hayes tarafından önerilen PROCESS makro kullanılmıştır. Araştırmanın bulgularına göre travma sonrası büyüme ile psikolojik sağlamlık arasındaki ilişkide bilişsel esneklik ve pozitif şemaların aracı rolünün istatistiksel olarak anlamlı olduğu görülmüştür
Keywords: Psychological Resilience; Cognitive Flexibility; Positive Schema; Posttraumatic Growth; Psikolojik Sağlmalık; Bilişsel Esneklik; Pozitif Şema; Travma Sonrası Büyüme